PENERAPAN NILAI HUMANISME DALAM PEMBELAJARAN AKIDAH AHKLAK PADA KURIKULUM MERDEKA DI SDN GLONGGONG 02 - Ahmad Muzaini; Taukhid Mubarok (CV. ADIBA AISHA AMIRA, 2024)
The purpose of this study is to promote the introduction of humanistic values in the lessons of Akida Akhlaq in order to promote civility towards the students of SDN Glonggong 02 school, and to identify supporting factors in the introduction ofhumanistic values.and to investigate the inhibiting factors.In order to learn about polite behavior toward students at SDN Glonggong 02, I worked in the politeness study group in Akidah Akhlaq.This study is a type of field study that is descriptive in nature.The study will be conducted at SDN Glonggong 02 and implementation is scheduled for November2023. And the study is in accordance with the independent curriculum. Bicause, the Merdeka curriculum incorporates the values of humanistic Islamic education: the value of cultivating common sense, included in the characteristics of capacity development, the principle of focusing on the student and paying attention to the results of feedback research and learning.was shown to be included. Individualistic values of independence. They are based on an independent curriculum paradigm. The value of the spirit of science, embodied in one of the aspects of achieving the goal of an independent curriculum, is to foster a love of learning. The values of pluralistic education are included in the Pancasila Profile Strengthening Project and the value of prioritizing function over symbols included in the dimensions of curriculum principles: , the principle of competence and the principle of mutual cooperation; of balance.